Effect of a Supportive Educational Program on Stress in Women with Endometrial Cancer - L Neisani Samani; AF Hoseini; M Modares Gilani; S Niroomand (نشریه پرستاری ایران, 2018)
Abstract Background & Aims: Endometrial cancer is the most common cancer of the female reproductive organs. Although widespread advances in the treatment of cancer has led to an increase in  patients’ longevity, the cancer diagnosis and subsequently invasive procedures such as surgery, radiation therapy and chemotherapy often result in unpleasant complications in their life. The aim of this study is to determine the effect of a supportive educational program on stress in women with endometrial cancer. Material & Methods: In this interventional study which has been done in 2014, 140 women with endometrial cancer were randomly selected from Imam Khomeini Hospital Complex in Tehran. The intervention was a supportive educational program conducted in 3 sessions in the intervention group. The control group received routine care. Data were collected by the demographic form and the Hari’s stress Inventory. The SPSS software version 16 and the t test, Chi-square and repeated measure analysis of variance were used to analyze the data. The level of significance was considered 0.05. Results: The stress mean score after the intervention, one month and two months later was significantly less than before the intervention(P<0.001).